2019
DOI: 10.1111/joor.12803
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorder pain, jaw noises and oral behaviours in an adult Italian population sample

Abstract: To evaluate the prevalence of temporomandibular disorder pain (TMD‐pain), temporomandibular joint (TMJ) noises, oral behaviours in an Italian adult population sample, their possible association with gender, oral behaviours, self‐reported facial trauma and orthodontic treatment. Subjects older than 18 years were recruited from general population in public spaces during their daily life. A specific questionnaire was developed to collect data on TMD‐pain, TMJ noises, oral behaviours, orthodontic treatment and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 38 publications
7
61
2
7
Order By: Relevance
“…The prevalence of TMJ trauma (8.9%) in the orofacial trauma universe is a new reference data in the Portuguese population, being in accordance with Iodice et al (7.2%). 5 The data from the present study (Table 1) this topic, with a 1.54:1 ratio, in line with Wright et al, 33 who reported a male-to-female ratio of 1.5:1. The mean age of 33.9 ± 14.7…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of TMJ trauma (8.9%) in the orofacial trauma universe is a new reference data in the Portuguese population, being in accordance with Iodice et al (7.2%). 5 The data from the present study (Table 1) this topic, with a 1.54:1 ratio, in line with Wright et al, 33 who reported a male-to-female ratio of 1.5:1. The mean age of 33.9 ± 14.7…”
Section: Discussionsupporting
confidence: 92%
“…3,4 The literature reports that TMJ trauma with orofacial traumatic events has incidence values from 7.2% to 24.5%. 4,5 In TMJ trauma, several structures can be compromised, from the bone components of the joint, such as the condyle and the glenoid fossa, to their articular surfaces, the articular disc or the synovial lining of the upper and lower joint space. 6 It can affect activities, such as mastication, the mandibular range of motion and intracapsular function, 6 as well as malocclusion.…”
mentioning
confidence: 99%
“…We performed a cross-sectional, descriptive study analysing patients who were diagnosed with TMD in Korea and utilised medical services at least once between January and December 2017. While previous studies have used the Research Diagnostic Criteria for TMD 19 or self-reported surveys 20 to diagnose TMD, limited studies have used ICD codes in administrative data. In this study, our research team operationally defined TMD as cases with an International Statistical Classification of Disease and Related Health Problems, 10th revision (ICD-10) code of K07.6 (TMJ disorders) or S03.4 (sprain and strain of jaw) as the main diagnosis under outpatient care.…”
Section: Methodsmentioning
confidence: 99%
“…Little interest has been shown, however, in the relationship between temporomandibular disorders (TMDs) and vision disorders, although both are very widespread in the Italian population. [1][2][3] The two systems, stomatognathic and oculomotor, represent the main exteroceptors of the head-neck district, capable of influencing the balance and behavior of patients. [4] The correlation between the two systems is expressed through three types of connection: anatomical through craniofacial sutures; [5,6] neurological through a connection between the encephalic nuclei such as the vestibular, trigeminal, oculomotor, and accessory nuclei; [4,[7][8][9][10][11] and functional through the muscle chains.…”
Section: Introductionmentioning
confidence: 99%